ANALISA DAMPAK BUDAYA DUALISTIS HUKUM TERHADAP PROSES PENEGAKAN HUKUM - Kusumah Putri, Annita Febriani; Senjaya, Oci (Universitas Tanjungpura, 2022)
In a country that has basic norms as a philosophy of social life, it has an important role in the formation and enforcement of applicable norms. In the process of social interaction, there is friction between individual interests and each other, making each problem complex. The emergence of community stigma is one of the law enforcement processes. Even the presence of left-wing opinions in a case can lead to the assumption that the law is just a formality that has no impact on anything. Or even the law only favors a certain group. So that the purpose of this paper is to analyze how the concept of law has a dualistic nature and how does the dualistic nature of law influence a culture. This analytical descriptive research uses normative juridical research, through library research stages and is supported by field research data in order to obtain primary, secondary, and tertiary legal materials and analyzed with qualitative juridical. The results of the study show that the case raised in this paper is the embodiment of a dualistic law and the effects of the dualistic nature of the law will create a different legal culture and the loss of unity in law enforcement.